Agricultural and applied economists' views on pre‐registration and pre‐analysis plans for empirical research - Grebitus, Carola; Hu, Wuyang (Journal of the Agricultural and Applied Economics Association, 2025)
Given the widespread credibility crisis of empirical research, disciplines including economics have increasingly turned attention to replicability‐seeking venues to enhance trust. One of these approaches is to pre‐register a study and prepare a pre‐analysis plan. There are promising benefits but also clear challenges, leading selected disciplines of economics to adopt pre‐registration and pre‐analysis plans for empirical research with caution. This study investigates how agricultural and applied economists view the current development of pre‐registration and pre‐analysis plans, and offers guidance for future advancements of these practices within the profession.